PENGARUH LABA AKUNTANSI, TOTAL ARUS KAS, DAN DIVIDEN PER SHARE TERHADAP HARGA SAHAM (Studi Empiris terhadap Perusahaan yang terdaftar dalam Indeks Kompas100 di BEI tahun 2016-2018) - Christian Van Berth Siregar; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
In carrying out stock investment activities in the capital market, investors need a variety of information to determine the best decision in choosing stocks. The information published by the company can affect the demand and supply of investors, then affect the stock price. In this study, the information used as a parameter to measure firm value from these financial statements is accounting profit, total cash flow, and dividend per share (DPS). The purpose of this research is to analyze the influence of the variable accounting profit, total cash flow, and dividend per share (DPS) on stock prices.The research was conducted using a quantitative approach and multiple linear regression analysis methods. The study population was 300 companies listed on the IDX in the Kompas100 index for the 2016-2018 period, with a sample size of 166 data after being selected using the purposive sampling method. Using secondary data obtained from financial reports through the website www.idx.com, www.investing.com, and related company websites. The results showed that accounting profit and dividend per share (DPS) had a significant effect on stock prices. Meanwhile, total cash flow has no significant effect on stock prices.